2022
DOI: 10.3389/fnins.2022.914556
|View full text |Cite
|
Sign up to set email alerts
|

Altered Regional Brain Glucose Metabolism in Diffuse Large B-Cell Lymphoma Patients Treated With Cyclophosphamide, Epirubicin, Vincristine, and Prednisone: An Fluorodeoxyglucose Positron Emission Tomography Study of 205 Cases

Abstract: BackgroundA growing number of neuroimaging studies reported that chemotherapy might impair brain functions, leading to persistent cognitive alterations in a subset of cancer patients. The present study aimed to investigate the regional brain glucose metabolism differences between diffuse large B cell lymphoma (DLBCL) patients treated with cyclophosphamide, epirubicin, vincristine, and prednisone and controls using positron emission tomography with 18F-labeled fluoro-2-deoxyglucose integrated with computed tomo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
(53 reference statements)
0
1
0
Order By: Relevance
“…Besides, 18 F-FDG PET/CT imaging could also be applied for the noninvasive appraisal of altered brain functions from the perspective of glucose metabolism. An increasing number of 18 F-FDG PET studies revealed that chemotherapy would lead to regional brain glucose metabolic abnormalities among lymphoma patients [ 15 18 ]. However, up till now, only a few researches have investigated the brain metabolic impairments in patients with pre-treatment lymphoma [ 19 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Besides, 18 F-FDG PET/CT imaging could also be applied for the noninvasive appraisal of altered brain functions from the perspective of glucose metabolism. An increasing number of 18 F-FDG PET studies revealed that chemotherapy would lead to regional brain glucose metabolic abnormalities among lymphoma patients [ 15 18 ]. However, up till now, only a few researches have investigated the brain metabolic impairments in patients with pre-treatment lymphoma [ 19 21 ].…”
Section: Introductionmentioning
confidence: 99%